2023
DOI: 10.1126/sciadv.adk2756
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionarily conserved serine protease network mediates melanization and Toll activation in Drosophila

Tisheng Shan,
Yang Wang,
Krishna Bhattarai
et al.

Abstract: Melanization and Toll pathway activation are essential innate immune mechanisms in insects, which result in the generation of reactive compounds and antimicrobial peptides, respectively, to kill pathogens. These two processes are mediated by phenoloxidase (PO) and Spätzle (Spz) through an extracellular network of serine proteases. While some proteases have been identified in Drosophila melanogaster in genetic studies, the exact order of proteolytic activation events remains controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Adipohemocytes play a role in lipid metabolism, and crystal cells contain a prophenoloxidase (ProPO) enzyme that participates in the melanization immune response (see below) [51,53,54]. Interestingly, as shown in Tenebrio, Manduca sexta, and Drosophila, the activation of the ProPO cascade and melanization pathway shares serine proteases with the Toll pathway [55][56][57]. Studies using single-cell RNA sequencing (scRNA-seq) identified subsets within lamellocytes that express fibroblast growth factor (FGF) receptor breathless and crystal cells that express FGF ligand branchless, which play a role in the response against parasitic wasps [52].…”
Section: Invertebrate Immune Cellsmentioning
confidence: 99%
“…Adipohemocytes play a role in lipid metabolism, and crystal cells contain a prophenoloxidase (ProPO) enzyme that participates in the melanization immune response (see below) [51,53,54]. Interestingly, as shown in Tenebrio, Manduca sexta, and Drosophila, the activation of the ProPO cascade and melanization pathway shares serine proteases with the Toll pathway [55][56][57]. Studies using single-cell RNA sequencing (scRNA-seq) identified subsets within lamellocytes that express fibroblast growth factor (FGF) receptor breathless and crystal cells that express FGF ligand branchless, which play a role in the response against parasitic wasps [52].…”
Section: Invertebrate Immune Cellsmentioning
confidence: 99%
“…Previous work with a Staphylococcus aureus low inoculum injection model has revealed a requirement of PPO1 and Sp7 for an uncharacterized killing activity, in addition to the role of melanization in a classical blackening reaction occurring at the wound site [8]. Recent in vitro work has documented Sp7 as being the major protease that cleaves PPOs [11]. In contrast to the situation with PAO1, the proliferation and dissemination of Aspergillus fumigatus depends solely on Hayan, and not on Sp7 [28].…”
Section: Differential Actions Of Melanization Effectors According To ...mentioning
confidence: 99%
“…Melanization involves a series of enzymatic reactions that are catalyzed by phenol oxidases, found as pro-proteins in the hemolymph, prophenol oxidases (PPOs). PPOs are cleaved into active POs by proteases such as Sp7 or Hayan, the latter being supposedly required for the activation of the three Drosophila PPOs [8][9][10][11]. In larvae, PPOs are stored in crystal cells and are released in the hemolymph by a JNK-dependent rupture of their cytoplasmic membranes [12].…”
Section: Introductionmentioning
confidence: 99%